2015
DOI: 10.1523/jneurosci.4892-14.2015
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Cortical Networks and Corticocortical Functional Connectivity Mediating Arbitrary Visuomotor Mapping

Abstract: Adaptive behaviors are built on the arbitrary linkage of sensory inputs to actions and goals. Although the sensorimotor and associative frontostriatal circuits are known to mediate arbitrary visuomotor mappings, the underlying corticocortico dynamics remain elusive. Here, we take a novel approach exploiting gamma-band neural activity to study the human cortical networks and corticocortical functional connectivity mediating arbitrary visuomotor mapping. Single-trial gamma-power time courses were estimated for a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
65
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(75 citation statements)
references
References 111 publications
2
65
0
1
Order By: Relevance
“…Corroborating this hypothesis, practice of S–R transformations led to a more distinct connectivity profile of the CON, involving strengthened pathways to the DAN, SAN and visual network, as well as higher within-network connectivity and better segregation from the DMN. Concerning the link between precuneus and SMA, which predicted practice-related RT decrease, a recent MEG study provided converging evidence for an essential involvement of this connection in S–R execution42. In this study, it was shown that Brodmann area 7 (precuneus/parietal cortex) exerts influence on Brodmann area 6 (SMA/premotor cortex) during the performance of S–R mappings, supporting the conclusion that stimulus inputs are first processed within the DAN and then transformed into appropriate motor responses via the DAN–CON pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Corroborating this hypothesis, practice of S–R transformations led to a more distinct connectivity profile of the CON, involving strengthened pathways to the DAN, SAN and visual network, as well as higher within-network connectivity and better segregation from the DMN. Concerning the link between precuneus and SMA, which predicted practice-related RT decrease, a recent MEG study provided converging evidence for an essential involvement of this connection in S–R execution42. In this study, it was shown that Brodmann area 7 (precuneus/parietal cortex) exerts influence on Brodmann area 6 (SMA/premotor cortex) during the performance of S–R mappings, supporting the conclusion that stimulus inputs are first processed within the DAN and then transformed into appropriate motor responses via the DAN–CON pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, several variants of connectivity have been applied to epilepsy (Amini et al , 2011, Epstein et al , 2014, Coito et al , 2015. It is interesting to note that Granger causality as implemented with auto-regressive models (Brovelli et al , 2004) or with a covariance-based approach (Brovelli et al , 2015) may not be radically different from a classical correlation analysis (Davey et al , 2013). What is likely to be a more influential choice is the fact of considering pair-wise or multivariate methods, which could remove indirect correlation arising from a common driving node (Kuś et al , 2004).…”
Section: Limitations and Future Directionsmentioning
confidence: 99%
“…Finally, to quantify the dynamics of reconfiguration among the three functional subnetworks, we inferred the evolution of network "flexibility" (following the same ideas developed in Braun et al, 2015). We defined the flexibility of a given brain region as the entropy associated with the probabilities of involvement in the three LCs (shown in Fig.…”
Section: Dynamic Reconfiguration Of Fc Subnetworkmentioning
confidence: 99%